2015
DOI: 10.7812/tpp/14-108
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Reduce Inappropriate Ionized Calcium Ordering Practices: A Quality-Improvement Project

Abstract: Context:The importance of an abnormal ionized calcium (iCa) measurement in noncritically ill patients is unclear. Furthermore, iCa monitoring is more expensive than measurement of total calcium and consumes more laboratory resources. We hypothesize that most iCa tests are ordered for routine monitoring in asymptomatic patients, and results do not influence clinical management.Objective: To characterize and to intervene on iCa testordering practices among our institution's hospital-based internal medicine clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…The magnitude of total reduction is within the range of reduction that has been seen in other studies17 22–27 29 32–38 looking to intervene on utilisation of low-value laboratory testing and the estimated range of overutilisation 2. Studies that used education alone around costs (through fee-display) and indications showed non-significant39 40 reductions, small reductions in utilisation34 or poor sustainability 17.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The magnitude of total reduction is within the range of reduction that has been seen in other studies17 22–27 29 32–38 looking to intervene on utilisation of low-value laboratory testing and the estimated range of overutilisation 2. Studies that used education alone around costs (through fee-display) and indications showed non-significant39 40 reductions, small reductions in utilisation34 or poor sustainability 17.…”
Section: Discussionsupporting
confidence: 57%
“…Prior studies have shown that higher numbers of routine laboratory tests are ordered in teaching hospitals where testing is ordered by rotating medical learners at different stages of training 20 21. To optimise laboratory testing, interventions that have attempted to address the above causes generally fall into three main categories: education, audit and feedback on ordering practices, and restrictive electronic medical record (EMR) mediated changes; with multifaceted interventions being associated with greater success 22–30…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, calcium indicators including total, ionized, and corrected calcium are influenced by different factors; therefore, it is not clear which of them is appropriate for assessing calcium status in ICU patients ( 9 ). Moreover, the findings of previous studies conducted about the relationship between hypocalcemia and adverse outcomes in ICU patients are controversial ( 5 , 10 - 12 ). In most studies, only one indicator of calcium status and its correlation with ICU outcomes were investigated.…”
Section: Introductionmentioning
confidence: 97%
“…They reported that laboratory ordering was reduced by 8% cumulatively over 3 years. Newman et al . also reported that a targeted education intervention substantially reduced the frequency of routine Ca testing, including in the ED setting.…”
Section: Discussionmentioning
confidence: 99%